The perception of health care workers and HIV-positive clients of HIV/AIDS care and treatment centres in Kogi state, North-central Nigeria, about the integrated model of HIV/AIDS service delivery - Akpu, Murphy Onuabuchi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.